Sosialisasi Undang-Undang Nomor 16 Tahun 2019 Perubahan atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Yuliana Yuli Wahyuningsih; Iwan Erar Joesoef; Dwi Desi Yayi Tarina; Satino Satino; Hermina Manihuruk (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Law Number 16 of 2019 represents a significant amendment to Law Number 1 of 1974 concerning Marriage, particularly regarding the minimum age for marriage. This regulatory change raises the minimum age for marriage for women from 16 to 19, bringing it on par with the minimum age for marriage for men. This age adjustment not only has legal implications but also represents a strategic step in preventing child marriage and protecting children's rights. One challenge in implementing this law is the limited public understanding of the purpose and impact of this regulatory change. Therefore, outreach is crucial to ensure that this regulation is truly understood, accepted, and complied with by the public. The outreach activities used a participatory approach involving various elements of society, including religious leaders, traditional leaders, village officials, teachers, and youth groups. This approach aims to create a space for dialogue and shared understanding so that legal messages can be more easily accepted. The results of the outreach indicate an increase in public legal awareness, particularly regarding the importance of delaying marriage until the specified minimum age is reached. Furthermore, outreach also fostered community support for enforcing the new regulations, ultimately contributing to strengthening child protection from the health, educational, and social risks often associated with early marriage. This study recommends the need for ongoing outreach with strategies that adapt to local cultural contexts, and are supported by regional government policies that align with national regulations. Synergy between the government, educational institutions, community organizations, and families is a key factor in ensuring the effective implementation of Law Number 16 of 2019 at the community level. Thus, changing the minimum age for marriage can truly have a positive impact on protecting the younger generation and achieving sustainable development goals.